Aktiviti Antimikrob Ekstrak Herba Andrographis Paniculata, Centella Asiatica Dan Orthosiphon Stamineus Serta Potensinya Sebagai Antimikrob Semula Jadi Dalam Daging Lembu Kisar [RM262. K79 2008 f rb]. - Koh, Chen Chung (2008)
Andrographis paniculata, Centella asiatica and Orthosiphon stamineus are three well-known herbs used in traditional Malaysian medicine for treatment of a wide range of diseases.